2005
DOI: 10.1016/j.immuni.2005.09.010
|View full text |Cite
|
Sign up to set email alerts
|

IL-6-STAT3 Controls Intracellular MHC Class II αβ Dimer Level through Cathepsin S Activity in Dendritic Cells

Abstract: We found IL-6-STAT3 pathway suppresses MHC class II (MHCII) expression on dendritic cells (DCs) and attenuates T cell activation. Here, we showed that IL-6-STAT3 signaling reduced intracellular MHCII alphabeta dimmer, Ii, and H2-DM levels in DCs. IL-6-mediated STAT3 activation decreased cystatin C level, an endogenous inhibitor of cathepsins, and enhanced cathepsin activities. Importantly, cathepsin S inhibitors blocked reduction of MHCII alphabeta dimer, Ii, and H2-DM in the IL-6-treated DCs. Overexpression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
143
1
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(160 citation statements)
references
References 47 publications
(65 reference statements)
11
143
1
2
Order By: Relevance
“…In this study, we found that eight different proteins interact with A2IC, by using a yeast twohybrid screen, including cathepsin S, SNX17, actin, RPS2, ZBTB4, OGDH, CCDC32, and PAPD4. An IL-6-gp130-STAT3-mediated increase in cathepsin S activity reduces the MHCII alpha/beta dimer in Dendritic cells and suppresses CD4 + T cell-mediated immune responses [23] . SNX17, a non-selfassembling protein, interacts with KRIT1, which plays a role in cell adhesion processes and intergrin signaling [24] .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that eight different proteins interact with A2IC, by using a yeast twohybrid screen, including cathepsin S, SNX17, actin, RPS2, ZBTB4, OGDH, CCDC32, and PAPD4. An IL-6-gp130-STAT3-mediated increase in cathepsin S activity reduces the MHCII alpha/beta dimer in Dendritic cells and suppresses CD4 + T cell-mediated immune responses [23] . SNX17, a non-selfassembling protein, interacts with KRIT1, which plays a role in cell adhesion processes and intergrin signaling [24] .…”
Section: Discussionmentioning
confidence: 99%
“…In another study, IL-10, produced by BCG infected macrophages, reduced cathepsin S expression levels, thereby overriding the ability of IFN-g to enhance class II MHC levels and promote T-cell recognition of infected cells [44]. However, another study found that IL-10 (and IL-6) enhanced the activity of various cathepsins, including cathepsin S and that IL-6 diminished DM levels [45]. Conceivably, this may have accounted for the improved presentation of DM-sensitive ''cryptic'' T-cell epitopes in IL-6-treated DC [43,46].…”
Section: Reciprocal Relationships Between Cytokines and Lysosomal Catmentioning
confidence: 95%
“…Although the cathepsin S promoter does not have a respectable STAT binding site, cathepsin S expression in VSMC was activated by IL-6 in a STAT-3-dependent process [37], which probably involved upregulation of IRF proteins. Indeed, mRNA for IRF-8 and IRF-3 were increased in the ascending aorta of MPS I mice, and these proteins may function in a similar fashion on the cathepsin S promoter as IRF-1 [27].…”
Section: Role Of Stat Proteins In Upregulation Of Mmp-12 and Cathepsin Smentioning
confidence: 97%